2013
DOI: 10.7860/jcdr/2013/5160.3735
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin Resistant Staphylococcus aureus Carriage amongst Health Care Workers of Critical Care Units in Kasturba Medical College Hospital, Mangalore, India

Abstract: Background: Outbreaks and prevalence of Methicillin resistant Staphylococcus aureus (MRSA) Nosocomial Infection (NI) among various populations have been well reported in literature, particularly those from developed countries. There is a paucity of information on carriage of MRSA in developing nations, including the carriage by critical healthcare givers who are potential transmitters.Aim and Objectives: Present study was aimed at establishing the carriage rate of MRSA among healthcare workers in the critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
(13 reference statements)
0
9
3
Order By: Relevance
“…Kanamycin also showed lower resistance compared with similar study in Serbia (90.3%) [ 27 ]. On the other hand, our finding was higher compared to studies conducted in India [ 28 ] ciprofloxacin (20%), and Gaza Strip erythromycin, tetracycline, gentamycin, clindamycin, and ciprofloxacin (19.6%), (9.8%), (3.9%), (3.92%), and (3.92%) respectively [ 17 ]. This resistance pattern of our finding might be due to excessive use of this antibiotics for many other infections and replacing of sensitive strains by resistance strains at the hospital settings.…”
Section: Main Textcontrasting
confidence: 84%
“…Kanamycin also showed lower resistance compared with similar study in Serbia (90.3%) [ 27 ]. On the other hand, our finding was higher compared to studies conducted in India [ 28 ] ciprofloxacin (20%), and Gaza Strip erythromycin, tetracycline, gentamycin, clindamycin, and ciprofloxacin (19.6%), (9.8%), (3.9%), (3.92%), and (3.92%) respectively [ 17 ]. This resistance pattern of our finding might be due to excessive use of this antibiotics for many other infections and replacing of sensitive strains by resistance strains at the hospital settings.…”
Section: Main Textcontrasting
confidence: 84%
“…Our reported rate of S. aureus colonization is also higher than that reported by other studies conducted in Arabic countries and other developing countries like Libya (12.4%; [30], India (17.5%; [31], West Bank of Palestine (20.8%; [11] and Kuwait (21%; [32]. …”
Section: Discussioncontrasting
confidence: 58%
“…The study showed relatively high prevalence of MRSA colonization among medical staff ( Table 2) which was in contrary to other study conducted in India reported comfortably low (2.5%) MRSA carriage among healthcare workers who were involved in the management of critically ill patients (Radhakrishna et al, 2013). Also other study reported high prevalence of colonization (19%) among their medical staff (Bisaga et al, 2008).…”
Section: Discussioncontrasting
confidence: 76%
“…ICUs are particularly appropriate for the rapid emergence and spread of MRSA. Patients in the ICU have special risk factors make them extremely vulnerable to healthcare associated MRSA (Radhakrishna et al, 2013).…”
Section: Introductionmentioning
confidence: 99%